2021
DOI: 10.21037/jgo-20-479
|View full text |Cite
|
Sign up to set email alerts
|

Serum calcium improved systemic inflammation marker for predicting survival outcome in rectal cancer

Abstract: Background: Systemic inflammation markers have shown prognostic values with variability in rectal cancer. Considering the association of serum calcium with inflammation, we aimed to examine whether it could improve systemic inflammation markers for survival prediction.Methods: We enrolled 508 patients with stage I to III rectal cancer who underwent curative resection. The cohort was grouped by corrected serum calcium (cCa), platelet-to-lymphocyte ratio (PLR), and CaPLR (a score model combining cCa with PLR) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Some studies have found that serum calcium levels can affect calcium signals within cells 9 , 10 and that changes in calcium ion levels can affect the body’s immune function. 11 , 13 In addition, evidence from a cohort study suggests that adequate serum calcium levels are associated with low levels of chronic inflammation. 14 Calcium ions involved in the immune defences against bacterial infections can be complex.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that serum calcium levels can affect calcium signals within cells 9 , 10 and that changes in calcium ion levels can affect the body’s immune function. 11 , 13 In addition, evidence from a cohort study suggests that adequate serum calcium levels are associated with low levels of chronic inflammation. 14 Calcium ions involved in the immune defences against bacterial infections can be complex.…”
Section: Discussionmentioning
confidence: 99%
“…The last but not the least, a relation of sCa with mortality caused by non-cardiovascular diseases cannot be excluded in the present study. Abnormalities of sCa have been reported to be associated with stroke, cancer and infection, which would also contribute to increased mortality 8 23 24…”
Section: Discussionmentioning
confidence: 99%
“…We divided the patients with rLN 5 mm and NLR 3 according to the previous studies 4,14 . The comparison between different predictive models shown in Table 5 was assessed through Akaike information criterion (AIC) likelihood ratio (LR), as previously described 7 …”
Section: Methodsmentioning
confidence: 99%
“… 4 , 14 The comparison between different predictive models shown in Table 5 was assessed through Akaike information criterion (AIC) likelihood ratio (LR), as previously described. 7 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation